Family guidance for the physical-therapeutic rehabilitation of patients with Parkinson's (RIAF. International Journal of Physical Activity, 2025)
Parkinson's disease, the second most common neurodegenerative disease, affects the central nervous system and the production of dopamine, a neurotransmitter essential for movement. This article highlights the importance of family support for people with Parkinson's and their loved ones. The aim is to guide the family for the rehabilitation of these people. It addresses how to provide emotional support, understand the stages of the disease and adapt to the challenges that arise. The research collects bibliographic information on Parkinson's and its family guidance, using academic databases such as Scielo, PubMed and Elservies. It is concluded that family guidance is essential for the rehabilitation of people with Parkinson's, by providing support, education and compassionate care, strengthening family ties.
Keywords: Parkinson's disease; Rehabilitation; family counseling